EDUKASI DAN WORKSHOP PEMBUATAN EMULGEL REPELLENT DI DESA PANYOSOGAN KUNINGAN JAWA BARAT SEBAGAI UPAYA PENCEGAHAN WABAH DEMAM BERDARAH - Srifiana, Yudi; Fujianti, Fujianti; Pahriyani, Ani (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Dengue fever is a disease that is still prevalent in tropical countries. Dengue fever were spread in Panyosogan village, Kuningan, West Jawa. Increased rainfall caused problems mosquitoes to breed even more rapidly in the Panyosogan village. The purpose of this activity is to provide education about the dangers of dengue fever and its prevention methods, as well as to empower the community to make natural mosquito repellent emulgel using lemongrass oil and cajeputi oil. This mosquito repellent emulgel is expected to be used as a natural and safe alternative for personal protection and can also be for entrepreneurship. There were 45 participants consisting of PKK team from the village. After explanations and education about dengue fever and basic insights into emulgel making techniques, there was an increase in knowledge of 34.93% between the pre-test and post-test. From these results, it can be conclude that the educational activities and workshop of repellent emulgel for dangue fever prevention are very beneficial for community empowerment in Panyosogan Village.